2021
DOI: 10.1142/s2737566821500110
|View full text |Cite
|
Sign up to set email alerts
|

Free Cash Flow, Managerial Ownership, and Agency Cost: A Nonlinear Evidence From Nigerian Quoted Consumer and Industrial Goods Firms

Abstract: This study focuses on a nonlinear approach in assessing the effect of free cash flow and managerial ownership on the agency cost of firms listed under the Consumer and Industrial Goods sector in the Nigerian Stock Exchange (NSE). Based on the extant theories, firms with high free cash flow are more exposed to agency costs. Existing literature however shows that managerial ownership could moderate this tendency. In this study, we argue that the extent to which managerial ownership moderates the effect of free c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Thus, this shows that managerial ownership and agency cost have a positive relationship. When a manager possesses a substantial stake in the company, he or she assumes full responsibility for all decisions, including those regarding the use of payout policy (Yero, Abubakar, Hamman & Saidu, 2021). He pursues his own objectives without concern for retribution (Guizani, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, this shows that managerial ownership and agency cost have a positive relationship. When a manager possesses a substantial stake in the company, he or she assumes full responsibility for all decisions, including those regarding the use of payout policy (Yero, Abubakar, Hamman & Saidu, 2021). He pursues his own objectives without concern for retribution (Guizani, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, free cash flow increases agency costs (Ahmed AL-Dhamari & Nor Izah Ku Ismail, 2014;Barger et al, 2019;Okofo-Dartey & Kwenda, 2021) and reduces asset utilization (Abdullah, 2002;Barger et al, 2019;Okofo-Dartey & Kwenda, 2021). Free cash flow is negatively related to assets utilization and the higher the free cash flow, the efficiency of assets utilization is significantly reduced (Iskandar et al, 2012;Yero et al, 2021). Previous studies generally revealed that an increase in free cash flow can lead to higher agency costs and a decrease in asset utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed different results in examining the mediating effect of foreign ownership in strengthening the effect of net profit margin on assets utilization. Some have found that asset utilization is significantly affected by foreign ownership (Iskandar et al, 2012;Yero et al, 2021). Foreign ownership is related to assets utilization but not significant (Iskandar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation